2019
DOI: 10.1002/ecy.2653
|View full text |Cite
|
Sign up to set email alerts
|

Forest fragmentation modulates effects of tree species richness and composition on ecosystem multifunctionality

Abstract: Forest fragments in highly disturbed landscapes provide important ecosystem services ranging from acting as biodiversity reservoir to providing timber or regulating hydrology. Managing the tree species richness and composition of these fragments to optimize their functioning and the deliverance of multiple ecosystem services is of great practical relevance. However, both the strength and direction of tree species richness and tree species composition effects on forest ecosystem multifunctionality may depend on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 42 publications
2
28
0
1
Order By: Relevance
“…Habitat loss and fragmentation have pervasive impacts on biodiversity and ecosystem function (Ewers and Didham 2006, Resasco et al 2016, Fletcher Jr et al 2018. Consequences of fragmentation arise from a loss of total area, increased isolation of remaining patches, and exposure to edge effects that initiate long-term changes in the structure and function of the species assemblages remaining in fragments (Haddad et al 2015, Hertzog et al 2019. Responses to fragmentation include reduced persistence within smaller fragments and decreased colonization of more isolated patches of habitat, thus lowering the rate of recolonization after extinction (Holt et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Habitat loss and fragmentation have pervasive impacts on biodiversity and ecosystem function (Ewers and Didham 2006, Resasco et al 2016, Fletcher Jr et al 2018. Consequences of fragmentation arise from a loss of total area, increased isolation of remaining patches, and exposure to edge effects that initiate long-term changes in the structure and function of the species assemblages remaining in fragments (Haddad et al 2015, Hertzog et al 2019. Responses to fragmentation include reduced persistence within smaller fragments and decreased colonization of more isolated patches of habitat, thus lowering the rate of recolonization after extinction (Holt et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Edge densities increase with fragmentation (Haddad et al, 2015) and are prominent drivers of insect composition (Murcia, 1995;Schmidt et al, 2017) and abundance (Debinski & Holt, 2000;Rand et al, 2006). In forest fragments, arthropod diversity has been shown to be strongly determined by tree species diversity, identify, and patch size (Hertzog et al, 2019Perring et al, 2021). The patch size effects are directly translated to edge effects which allow coexistence of both forest and matrix-species (e.g., Rand et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental drivers acting at larger spatial scales, that is, beyond the stand scale, may also affect forest functioning and biodiversity. Hertzog et al (2019) showed that habitat fragmentation mediated tree species diversity effects on forest functioning, likely through edge and connectivity effects. Edge effects arise when abiotic conditions close to boundaries between different habitats differ from those within their cores (Schmidt et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A web application (available through: https://gfoe2 016.shiny apps.io/treew eb_synth esis2/) was also developed for readers and practitioners to explore the impact of other perspectives of forest management on forest ecosystem services. This work builds on previous studies (Baeten et al, 2019;Hertzog et al, 2019) by explicitly considering trade-offs and synergies between multiple functions and the diversity of associated taxa at both the plot and the landscape scale, but also by confronting different stakeholder perspectives to provide direct inputs to management and policy discussions on the benefits of mixing tree species under different levels of fragmentation.…”
Section: Introductionmentioning
confidence: 99%